Undeniable evidence of halokinesis in the Huallaga Basin – Peru - Cotrina Cubas, Jimmy (2021)
The Huallaga basin has been studied and tectonically interpreted as typical fold and thrust belt of thin skin, however, the present study led us to the conclusion that this region had experimented the classic characteristics of halokinesis, the majorities of which had developed in the Jurassic unrelated to any compressional tectonic events. Evidenced by the numerous outcrops from the salt domes, described and mapped along the sub-Andean and with interpretation of 2D seismic acquired by diverse petroleum companies. Finally, special emphasis has been placed on the analysis of those key factors that explain the movement of salt, geometry and deformation of the different structures recognized and interpreted in seismic sections.